Establishment of a panel of in-house polyclonal antibodies for the diagnosis of enterovirus infections - Kotani, Osamu; Iwata-Yoshikawa, Naoko; Suzuki, Tadaki; Sato, Yuko; Nakajima, Noriko; Koike, Satoshi; Iwasaki, Takuya; Sata, Tetsutaro; Yamashita, Teruo; Minagawa, Hiroko; Taguchi, Fumihiro; Hasegawa, Hideki; et al. (Neuropathology, 2015)
The aim of this study was to establish a reliable method of virus detection for the diagnosis of critical enterovirus infections such as acute infective encephalitis, encephalomyelitis and myocarditis. Because histopathological and immunohistochemical analyses of paraffin‐embedded tissues play an important role in recognizing infectious agents in tissue samples, six in‐house polyclonal antibodies raised against three representative enteroviruses using an indirect immunofluorescence assay and immunohistochemistry were examined. This panel of polyclonal antibodies recognized three serotypes of enterovirus. Two of the polyclonal antibodies were raised against denatured virus particles from enterovirus A71, one was raised against the recombinant VP1 protein of coxsackievirus B3, and the other for poliovirus type 1 were raised against denatured virus particles, the recombinant VP1 protein and peptide 2C. Western blot analysis revealed that each of these antibodies recognized the corresponding viral antigen and none cross‐reacted with non‐enteroviruses within the family Picornaviridae. However, all cross‐reacted to some extent with the antigens derived from other serotypes of enterovirus. Indirect immunofluorescence assay and immunohistochemistry revealed that the virus capsid and non‐structural proteins were localized in the cytoplasm of affected culture cells, and skeletal muscles and neurons in neonatal mice experimentally‐infected with human enterovirus. The antibodies also recognized antigens derived from recent clinical isolates of enterovirus A71, coxsackievirus B3 and poliovirus. In addition, immunohistochemistry revealed that representative antibodies tested showed the same recognition pattern according to each serotype. Thus, the panel of in‐house anti‐enterovirus polyclonal antibodies described herein will be an important tool for the screening and pathological diagnosis for enterovirus infections, and may be useful for the classification of different enterovirus serotypes, including coxsackieviruses A and B, echoviruses, enterovirus A71 and poliovirus.